2019
DOI: 10.1039/c9sc03291f
|View full text |Cite
|
Sign up to set email alerts
|

Low-order many-body interactions determine the local structure of liquid water

Abstract: Two-body and three-body energies, modulated by higher-body terms and nuclear quantum effects, determine the structure of liquid water and require sub-chemical accuracy that is achieved by the MB-pol model but not by existing DFT functionals.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 55 publications
6
75
0
Order By: Relevance
“…MB-pol [54][55][56] and MB-DFT 43 are explicit many-body models derived from the many-body expansion (MBE) of the energy, which represents the energy of a system of N "bodies" (i.e., distinct atoms or molecules) as the sum of all the individual n-body contributions, with n ≤ N. 57 The MBE is formally expressed as…”
Section: Explicit Many-body Models: Mb-pol and Mb-dftmentioning
confidence: 99%
“…MB-pol [54][55][56] and MB-DFT 43 are explicit many-body models derived from the many-body expansion (MBE) of the energy, which represents the energy of a system of N "bodies" (i.e., distinct atoms or molecules) as the sum of all the individual n-body contributions, with n ≤ N. 57 The MBE is formally expressed as…”
Section: Explicit Many-body Models: Mb-pol and Mb-dftmentioning
confidence: 99%
“…Overall, methodology has made a key progress and will continue in this direction for all types of polarizable force fields as the accessible computer power quickly increases reducing therefore the computational gap with additive potentials. Whereas specialized highly accurate water potentials based on many-body expansions emerge such as MBPOL (Riera et al, 2019) and allow for a better understanding of fine physical effects in clusters and bulk water, the availability of general polarizable force fields such as AMOEBA offering water (Ren and Ponder, 2003), ions, organochlorine compounds (Mu et al, 2014), proteins and nucleic acids (Shi et al, 2013; Zhang et al, 2018) now enables performing enough sampling to achieve highly accurate and biologically meaningful simulations. The Drude approaches parametrization is expanding as well (Lamoureux et al, 2003; Chowdhary et al, 2013a,b; Lopes et al, 2013).…”
Section: Are Polarizable Simulations Computationally Tractable?mentioning
confidence: 99%
“…The MB-DFT PEFs generalize the MBE formalism adopted to develop the MB-pol PEF of water by replacing the 2-body (2B) and 3-body (3B) terms, which were originally calculated at the CCSD(T)/CBS level of theory, with corresponding terms calculated using an arbitrary density functional. 53 It has been shown that the MB-DFT PEFs closely reproduce the structural properties of liquid water calculated from fully ab initio MD simulations carried out with the same density functional. 53 The MB-DFT family of hybrid data-driven/physics-based PEFs is particularly appealing for quantum mechanics/molecular mechanics (QM/MM) simulations of systems that are either too computationally expensive to be treated at a fully quantum-mechanical (QM) level or cannot be described using molecular mechanics (MM) models since they involve rearrangements of chemical bonds.…”
Section: Introductionmentioning
confidence: 78%
“…53 It has been shown that the MB-DFT PEFs closely reproduce the structural properties of liquid water calculated from fully ab initio MD simulations carried out with the same density functional. 53 The MB-DFT family of hybrid data-driven/physics-based PEFs is particularly appealing for quantum mechanics/molecular mechanics (QM/MM) simulations of systems that are either too computationally expensive to be treated at a fully quantum-mechanical (QM) level or cannot be described using molecular mechanics (MM) models since they involve rearrangements of chemical bonds. Likewise, while ML approaches can, by construction, model bond rearrangements, their behavior is highly dependent on the composition the datasets and level of theory used in the training process.…”
Section: Introductionmentioning
confidence: 78%